Functional avidity of anti-B7H3 CAR-T constructs predicts antigen density thresholds for triggering effector function - Marta Barisa; Henrike P. Muller; Elisa Zappa; Rivani Shah; Juliane L. Buhl; Benjamin Draper; Courtney Himsworth; Chantelle Bowers; Sophie Munnings-Tomes; Marilena Nicolaidou; Sonia Morlando; Kathleen Birley; et al. (Nature Communications)
Abstract Chimeric Antigen receptor T cell (CAR-T) treatments for solid cancers have been compromised by limited expansion and survival in the tumor microenvironment following interaction with antigen-expressing target cells. Using B7H3 as a model antigen with broad clinical applicability, we evaluate the relationship between the antibody/antigen affinity of three clinical candidate binders and the three following characteristics: cellular avidity, duration of sustained cytotoxicity in tumoroid re-stimulation assays, and in vivo anti-tumoral responses. Next, BEHAV3D video microscopy is used to assess CAR-T cell interaction with tumor cells at single cell resolution. These data are consistent with a threshold avidity of CAR-T / tumor cell interaction and target cell B7H3 expression level, where enhanced functionality is characterized by longer cumulative CD8+ CAR-T / tumor target interaction times, CAR-T cell expansion and sustained tumor control. Lower checkpoint receptor expression does not correlate with enhanced anti-tumor function. These results provide further insights into design of anti-B7H3 CAR-T cells for antigen-dim cell targeting, and avoidance of antigen-dim tumor relapse.